Pengaruh Senam Lansia terhadap Hipertensi di Wilayah Kerja Puskesmas Krueng Barona Jaya Aceh Besar - Miftahul Jannah; Urip Pratama; Mansuriza Mansuriza (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Hypertension in the elderly is one of the common and significant health problems. The purpose of this study was to determine the effect of elderly exercise on hypertension in the working area of ​​the Krueng Barona Jaya Aceh Besar Community Health Center. The study method applied was a quasi-experimental design through a pre-test-post-test approach with a total population of 413 hypertension sufferers and a total sample of 15 people. The sample collection method was through Snowball Sampling. This research was conducted on April 20-24, 2025 in Meunasah Village, Papeun, with the research instrument in the form of an observation sheet with a measuring instrument using a sphygmomanometer. First, blood pressure was measured before the intervention, using a blood pressure monitor. Next, the elderly were given 20 minutes of exercise, followed by another 30-minute evaluation to assess changes in blood pressure. The results showed that before being given elderly exercise activities, the average systolic blood pressure of respondents was 179.60 mmHg and diastolic blood pressure was 102.73 mmHg, while after being given elderly exercise activities, the average systolic blood pressure of respondents was 170.80 mmHg and diastolic pressure was 92.80 mmHg with a difference of 8.8 mmHg systolic blood pressure and 10.13 mmHg diastolic blood pressure using a paired t-test of ρ value 0.000 (ρ <0.05). The conclusion is that there is an effect of elderly exercise on hypertension. It is hoped that hypertension sufferers and researchers will carry out routine elderly exercise activities, educational institutions will provide books on hypertension and complementary materials to increase students' knowledge and insight, and further research will be able to use the findings of this study as reference material and can improve this study through different variables.